Longitudinal development of risk-taking and self-injurious behavior in association with late adolescent borderline personality disorder symptoms. (March 2019) - Ghinea, Denisa; Koenig, Julian; Parzer, Peter; Brunner, Romuald; Carli, Vladimir; Hoven, Christina W.; Sarchiapone, Marco; Wasserman, Danuta; Resch, Franz; Kaess, Michael
Highlights: Increased risk for BPD in adolescents engaging in self-injurious and risk-taking behavior. Maintenance of self-injurious behavior is associated with the highest odds ratios for BPD. Longitudinal study on the predictive value of self-injurious and risk-taking behavior for BPD in adolescents. Data from the German Saving and Empowering Young Lives in Europe cohort (SEYLE). Abstract: Self-injurious behavior and risk-taking behaviors are associated with adolescent borderline personality disorder (BPD). Developmental trajectories of self-injurious and risk-taking behavior in predicting BPD have not been fully understood. The aim of the present study was to examine self-injurious and risk-taking behavior development and their prospective influence on BPD symptoms in adolescence. Data ( n = 506; 62.06 % females, 14.53 years) from the German Saving and Empowering Young Lives in Europe cohort were analyzed. Self-injurious and risk-taking behaviors were assessed at baseline and one-year follow-up. BPD symptoms were assessed at two-year follow-up. In fully adjusted stepwise binominal regression analyses, recent onset, termination and maintenance of risky alcohol use and self-injurious behavior remained as significant predictors of BPD. Highest ORs were found for alcohol termination and maintenance of self-injurious behavior. Other facets of risk-taking behavior were not associated with increased ORs of BPD symptoms at two-year follow-up. These findings highlight the importance of self-injurious behavior and specific facets of risk-taking behavior in the development of adolescent BPD. Clinicians should focus on efforts in preventing adolescents from risk-taking and self-injurious behavior, since engaging in young age and therefore in potentially longer periods of these behaviors is associated with the highest risk of BPD.